Optimising arrival management in air traffic control - Yang, L (2022)
Efficient landing is a key component of improving air transport, both for passengers' experience and fuel consumption. With just two runways, Heathrow airport was running at 98% capacity before the pandemic. The existing queuing system allows buffer time for the aircraft to land on one runway, but this can add delays to journeys and be fuel inefficient. With the recovery of the travel industry after the 2020 pandemic, improving landing procedures remains a pertinent problem to NATS (who manages all the air traffic in UK airspace). In this thesis, we develop alternative methods to sequence aircraft as they approach for landing at Heathrow.